ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DAN HARGA JUAL DENGAN METODE JOB ORDER COSTING PADA UMKM PANGESTU PRODUCTION DI GROGOL TAHUN 2022 - Safitri, Rika; Zaman, Badrus; Linawati, Linawati (Universitas Nusantara PGRI Kediri, 2023)
This research is motivated by problems that UMKM has in financial accounting calculations due to limited knowledge about cost classification, which must be included in the calculation of the cost of production so that the resulting selling price is less than optimal. This study aims to determine the accuracy in classifying costs in calculating the cost of production and determining the selling price of the screen printing t-shirt product applied by Pangestu Production whether or not it is appropriate with cost accounting. The research object focused on cost reports during the screen printing t-shirt production process. This research uses a quantitative approach with descriptive methods. The conclusion of this study is that the calculations applied by Pengstu Production and the calculations by the researchers have a slight difference, this is because the company has several costs when production is not included, this results in the selling price applied by the company being less than optimal. For manual t-shirt screen printing, based on analysis calculations, the selling price is IDR 61,800 while the company selling price is IDR 61,000. The cause of the difference in selling prices is that the company does not calculate depreciation costs and some costs of auxiliary raw materials are ignored.